Karakteristik Lingkungan Hutan untuk Terapi Kesehatan di Taman Hutan Raya Bunder, Gunungkidul, Daerah Istimewa Yogyakarta - Pertiwi, Serly Andini; Nurjani, Emilya; Hadisusanto, Suwarno (Universitas Gadjah Mada, 2025)
Healing forests maintain health through preservative practices, allowing benefits to emerge when site conditions support the practices. Therefore, this research aimed to identify the biophysical components and physical elements of the healing forests in Bunder Grand Forest Park (GFP). This research adopted observation methods and spatial analysis to characterize the healing forests' biophysical components and physical elements. The results showed that Bunder GFP had a diverse biodiversity and a distinctive landscape with the potential to provide comfort for visitors. It also met the criteria outlined in SNI 9006:2021, with medium thermal comfort levels. This research suggested vegetation enrichment to enhance the park's therapeutic potential, decrease noise, and increase thermal comfort. Additionally, the existing water features, karst rocks, and mixed forest vegetation can be used as media for sensory stimulation, further supporting health therapy.